Torque, power and cutting force prediction model by using response surface method and factorial design - Kadirgama K.; Abou-El-Hossein K.A. (EuroJournals, Inc., 2023)
This paper describes the development of a response models (cutting force,torque and power) for milling 618 stainless steel utilizing response surface methods. The both models are developed in terms of cutting speed, feed rate, axial depth and radial depth. The cutting force,power and torque contours have been generated from these model equations and are shown of different plots. The model generated show that the cutting force reach the maximum value when cutting speed decreased and , feed rate, axial depth and radial depth are increased. The torque reaches the maximum value when cutting speed decreased and, feed rate, axial depth and radial depth are increased. The plot which shows the relationship between the torque and cutting speed been developed. From the plot, the cutting forces reach the highest value when the torque increased. The power model show increases when cutting speed, feed rate, axial depth and radial depth are increased. Factorial design been used to find out the effect of the torque and power to the cutting force. The value of the predicted value with considers covariates much more closer compare with the prediction without considered. The second order is more accurate based on the variance analysis and the predicted value is closer with the experimental result. EuroJournals Publishing, Inc. 2007.